Dynamic behavior and mechanism analysis of tip wetting process under flash boiling conditions. (1st January 2022) - Xiao, Di; Qiu, Shuyi; Zhang, Xuan; Zhang, Yijia; Li, Xuesong; Hung, David; Xu, Min
Highlights: Dynamic behavior and mechanism of tip wetting were analyzed under flash boiling condition. Dribble induced wetting dominant effect during tip wetting process. Flash boiling would increase the fuel film, while strong evaporation can eliminate tip wetting. Abstract: The increasingly stringent emission regulations have required that the State-of-the-art internal combustion engines operated with minimum particulate matters produced. Flash boiling spray is considered to be potential technology for achieving high efficiency combustion, with its benefit of improving fuel-air mixing process in cylinders and eliminating spray-wall impingement. On the other side, it is believed that flash boiling would also enhance the injector tip wetting phenomenon since the widened spray plume would interact with the pre-hole more frequently, causing tip sooting and deposits. However, understanding of the physics related to the tip wetting film formation, propagation and evaporation is still lacking in the existing literature. This investigation focused on a two-hole gasoline direct injection (GDI) fuel injector, and its tip wetting characteristics were analyzed with optical means. High-speed imaging was used to illustrate the film dymanics in the near field, and laser-induced fluorescence was used to capture clear footprints of the tip film. Various boundary conditions, such as the fuel temperature, ambient pressure, and injection durations were investigated to figure out their impacts on the tip wetting process. It was found that the tip wetting process could be divided into two stages, namely wide plume induced wetting and dribble induced wetting, among which the fuel dribble was the primary cause of tip wetting. Besides, the impact of flash boiling spray on tip wetting could be analyze in two aspects. The enhanced wide plume effect and finner dribble would significantly increase the fuel deposited onto the tip, while the strong evaporating nature can help eliminate negative tip wetting effects from flash boiling atomization.